Psychometric validity and reliability of the Turkish version of the questionnaire for urinary incontinence diagnosis in women with urinary incontinence - Emrullah Akay; Osman Murat Güler; Hilal Künkül Bayraktar; Alime Dilayda Uzun Gül; Alper Türkoğlu (BMC Women's Health)
Abstract Background The aim of this study was to evaluate the psychometric validity and reliability of the Turkish version of the Questionnaire for Urinary Incontinence Diagnosis (QUID), which was developed for women with urinary incontinence. Methods This cross-sectional, methodological study included 600 female participants aged 18 years and above with Turkish reading and writing skills. Psychometric methods comprised correlation analysis, internal consistency (Cronbach’s alpha), test–retest reliability, and receiver operating characteristic (ROC) curve analysis. The QUID, King’s Health Questionnaire (KHQ), and Incontinence Severity Index (ISI) were administered consecutively to assess construct validity and diagnostic performance. Statistical significance was set at p < 0.05. Results The Turkish version of the QUID demonstrated high validity and reliability in distinguishing stress and urge urinary incontinence. The QUID scores were significantly positively correlated with the KHQ and ISI scores, indicating consistency with the established measures (p < 0.05). The test‒retest reliability analysis confirmed that the QUID scale provided consistent results over time, with high internal consistency reflected by a Cronbach’s alpha coefficient of 0.858, which suggests the questionnaire’s stability and reliability for repeated measurements. Additionally, receiver operating characteristic (ROC) curve analyses revealed area under the curve (AUC) values ranging from 0.886 to 0.996 for each subscale, highlighting the high discriminative power of the QUID in distinguishing different types of urinary incontinence effectively. Conclusions The results of this study indicate that the Turkish version of the QUID is a reliable and valid tool for diagnosing urinary incontinence in clinical practice and may contribute positively to patients’ quality of life by providing an accurate diagnosis. Trial registration Not applicable.